VOTING OF THE EUROPEAN PARLIAMENT MEMBERS: WHY THEY REMAIN LOYAL TO NATIONAL STATES? - Skusevičienė, Dorota (Politologija, 2015)
The article discusses factors, determining loyalty of the European Parliament members, which is marginalized in most of researches on the European Parliament. The initial assumption holds that as given the rates of loyalty to the national states are high it is groundless to assess it as a neutral variable. Loyalty of the European Parliament members to national states can significantly contribute to the studies of European Parliament’s internal relations and power contribution.The first section of this article presents and analyses main insights of the influence of national parties and political groups on the voting behavior of the European Parliament members, justifying objective reasons which caused marginalization of importance of the European Parliament members’ loyalty to national states. It should be noted that the European Parliament members, like most of other politicians, have fixed set of objectives forming their choices. Goals of re-election, positions and policy (leading to power gains/losses) are leading. In the hands of national parties and political groups these goals become instruments of pressure and enforcement, determining behavior of the European Parliament members. National parties controlling the access of candidates to the electoral lists and defining their position on those lists gain extreme importance in the competition for loyalty. Since political groups of the European Parliament have dominant political force for the second objective of the parliament members each of them have an interest in maintaining balance between loyalty to the national party and particular political group. Loyalty to national states loses its importance as it has minimal influence on the success of achieving objectives of the parliament members.The second section is devoted to the research of links between voting of European Parliament members and their national states, more specifically – to the analysis of European Parliament members’ loyalty to their national states. Lithuania is chosen as a case study. The fact that loyalty to the national states during 2004–2009 and 2009–2014 terms of the European Parliament is over 85 % indicates that this variable should not be seen as accidental or insignificant. It is argued that loyalty to the national state mainly reflects voting unity of national delegation. The rest of this section analyzes factors which can explain why, despite the fact that national delegation is very diverse in the context of left-right ideological divide, rates of loyalty to the national states, demonstrated by the national delegations, remain very high.The article concludes stating that loyalty of European Parliament members to their national states is a valuable source of data for the analysis of the party behavior in the European Parliament as well as outside it and should not be overlooked.